Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/oby.22728
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lifestyle and Hypertriglyceridemic Waist Phenotype in the PREDIMED‐Plus Study

Abstract: Objective The hypertriglyceridemic waist (HTGW) phenotype is characterized by abdominal obesity and high levels of triglycerides. In a cross‐sectional assessment of PREDIMED‐Plus trial participants at baseline, HTGW phenotype prevalence was evaluated, associated risk factors were analyzed, and the lifestyle of individuals with metabolic syndrome and HTGW was examined. Methods A total of 6,874 individuals aged 55 to 75 with BMI ≥ 27 and < 40 kg/m2 were included and classified by presence (HTGW+) or absence (HTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…Thus, Lemieux et al call this index “the hypertriglyceridemic waist phenotype”, who demonstrated that it was also associated with an increased prevalence of type 2 diabetes in adult men and women, while Fernández-García et al . related it to a sedentary lifestyle, which is an important risk factor in the development of obesity-related metabolic diseases 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Lemieux et al call this index “the hypertriglyceridemic waist phenotype”, who demonstrated that it was also associated with an increased prevalence of type 2 diabetes in adult men and women, while Fernández-García et al . related it to a sedentary lifestyle, which is an important risk factor in the development of obesity-related metabolic diseases 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…For this goal, the MD is intended as that diet regimen in use in the Mediterranean basin, which is fundamentally made up of local fresh seasonal non-industrial ingredients with a nutrient-respectful cooking manner and composed of three meals a day with a very light breakfast, a lunch, and a dinner-the latter both articulated into three courses. For a greater punctual precision, we want to mainly refer to the MD components described by the 14 items included in the MEDAS PREDIMED nutritional intervention carried out in Spain from 2003 to 2011 [13], which was recently validated [14] and is currently used in nutritional studies with MD as a topic [15].…”
Section: Finality Criteria Scheme and Drafting Methods Of This Reviewmentioning
confidence: 99%
“…Indeed, a multi-center randomized trial showed that higher adherence to MedDiet is associated with decreased overweight/obesity prevalence, reflected by a lower score of body mass index [85]. Likewise, a recent study conducted on participants with abdominal obesity showed that adherence to MedDiet is associated with low peripheral glucose, total cholesterol and low-density lipoprotein (LDL) cholesterol levels [86]. As far as epigenetics is concerned, MedDiet has been suggested to exhibit positive effects on cardiovascular diseases, including obesity, through the modulation of the circadian locomotor output cycles protein kaput (CLOCK) gene, which is well-known to regulate glucose metabolism [87].…”
Section: Polyphenols As the Most Abundant Antioxidant In Meddietmentioning
confidence: 99%